CGIAR report concerning centers’ implementation of their Article 15 Agreements: A submission to the eleventh session of the governing body of the international treaty on plant genetic resources for food and agriculture - CGIAR Genebanks Accelerator (2025)
This report provides an update on the status of the plant genetic resources for food and agriculture (PGRFA) collections maintained by the eleven CGIAR Centers that signed Article 15 agreements with the Governing Body of the International Treaty on Plant Genetic Resources for Food and Agriculture (Plant Treaty) in 2006.